Optimized Well Construction Cost Estimate in South of Iraqi Fields/ Case Study from Zubair Field - Hussein, Maher Falih; Shabib, Ahmed Rahman; Abood, Salah Faisal (Journal of Petroleum Research and Studies, 2021)
Cost estimation and control is a crucial activity for well engineering and construction. In addition to the technical preparation before drilling an oil well, well construction cost is one of the essential activities leading to AFE (authorization for expenditure). Recently the probabilistic method for cost estimate became necessary for understanding the risk and uncertainty of a certain cost range instead of a single (deterministic) value. This work describes the main types of drilling contracts have been used in Basra oilfields and discusses the principles of well construction cost estimate according to those contracts. In addition, it summarize the relevant cost breakdown for drilling operations. The research also illuminates the probabilistic method for effective well cost estimating along with deterministic method. the study subdivided the process of well construction into segments for cost tracking, emphasized the main aspects influence the well cost and leading to a methodology that can be applied by the operator for onshore well in the south of Iraqi fields. The methodology used in this work includes, first, analyzing data from offset wells to facilitate the possible cost out comes, and second, subdivide the well construction activities into fixed costs, time dependent and depth dependent costs. A probabilistic model (Monte Carlo simulation) for cost estimating is constructed using @ Risk software. The results released for risked drilling operation, which includes the NPT. While revising the historical cost performances in Zubair field, it has found that the best practices and lesson learned of the previous activities has significantly contributed in time and cost reduction of well operation. The findings of this work contributes to improve the decision-making by managers for best investment, enhance the planning for next activities and confident choice of well budget. It also helps to investigate the critical factors and actions that can be applied on operational and contractual parameters to achieve cost reduction. A case study from Zubair field will be presented in order to illuminate the mentioned points.